2018
DOI: 10.3390/molecules23010155
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Safener Activity of Novel Methyl (R)-N-Benzoyl/Dichloroacetyl-Thiazolidine-4-Carboxylates

Abstract: A series of novel methyl (R)-N-benzoyl/dichloroacetyl-thiazolidine-4-carboxylates were designed by active substructure combination. The title compounds were synthesized using a one-pot route from l-cysteine methyl ester hydrochloride, acyl chloride, and ketones. All compounds were characterized by IR, 1H NMR, 13C NMR, and HRMS. The structure of 4q was determined by X-ray crystallography. The biological tests showed that the title compounds protected maize from chlorimuron-ethyl injury to some extent. The ALS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Compound 3 competed with clorimuron-ethyl at the target active site by preventing the herbicide from acting on the ALS active pocket, thereby causing clorimuron-ethyl to lose its action. The ALS enzyme activity test results also showed that compound 3 almost reversed clorimuron-ethyl-triggered inhibition …”
Section: Molecular Docking Analysis Of Safenersmentioning
confidence: 89%
See 1 more Smart Citation
“…Compound 3 competed with clorimuron-ethyl at the target active site by preventing the herbicide from acting on the ALS active pocket, thereby causing clorimuron-ethyl to lose its action. The ALS enzyme activity test results also showed that compound 3 almost reversed clorimuron-ethyl-triggered inhibition …”
Section: Molecular Docking Analysis Of Safenersmentioning
confidence: 89%
“…Chlorimuron-ethyl, an ALS inhibitor, suppresses branched chain amino acid synthesis by preventing isoleucine, leucine, and valine syntheses, ultimately causing weed death . However, chlorimuron-ethyl causes injury to legumes, and its residues may inhibit the growth of subsequent crops such as maize. , Through active substructure splicing, a series of novel methyl (R)- N -benzoyl/dichloroacetyl-thiazolidine-4-carboxylates was designed and synthesized . Bioactivity tests showed that the target compounds exhibited some protection against chlorimuron-ethyl damage on maize (Figure b).…”
Section: Structure–activity Relationship (Sar) Of Novel Herbicide Saf...mentioning
confidence: 99%
“…R-28725 [2,2-dichloro-1-(2,2-dimethyloxazolidin-3-yl)­ethan-1-one] was a mature safener with good biological activity, and thiazolidines are thought to have similar chemical properties to R-28725 as a result of bioisosterism. , Zhao et al designed and synthesized a series of thiazolidine-4-carboxylates bound by different groups at the N-3 position, retaining the thiazolidine ring as the parent skeleton structure (Scheme ) based on active substructure splicing and bioisosterism. The compounds were shown to have certain safener activities in maize and increased the ALS enzyme activity.…”
Section: Design Of Novel Herbicide Safeners In Recent Yearsmentioning
confidence: 99%
“…16 Directed synthesis studies have shown that subtle modifications to the structure of CSA can affect its bioactivity, identifying the retention of the cyclopropyl group as a chemical feature required for its safener activity. 17,18 Therefore, one explanation for CSA's species specificity is that this safener is metabolised to different derivatives that vary in their protective activity in different crops. To evaluate this hypothesis, we now report on the activity and associated metabolism of CSA in safener-responsive maize and nonresponsive wheat.…”
Section: Introductionmentioning
confidence: 99%